(3QSGFd ehMOjIs
(3ChdgG (B:s
(3hChd eG ajgG QSGdI ef eNGWHI LeghQjI ai JbOje bGFO Ydi GdCSWhd hGTZGd GdHMQ s
(3BNQgG (B:s
(3jfJgi HGKfGA QSGdI (B" (3hai JbOje (B" (3cJH Gddg dce CefG jYe LejY Ch WGfce s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs